Improved symptoms and signs of refractory interstitial cystitis in women after intravesical Nanofat plus platelet-rich plasma grafting: A pilot study. Issue 6 (10th June 2022) - Hung, Man-Jung; Tsai, Ching-Pei; Ying, Tsung-Ho; Chen, Gin-Den; Su, Hong-Lin; Tseng, Chih-Jen
Abstract : Interstitial cystitis/bladder pain syndrome (IC/BPS) is characterized by bladder pain accompanied by irritative urinary symptoms, and typical cystoscopic and histological features. In this pilot study, we assessed the impact of lesion-targeted bladder injection therapy using a biocellular regenerative medicine on patients with refractory IC/BPS. The medicine, which was an autologous emulsified fat (Nanofat) and platelet-rich plasma (PRP) combination, was prepared intraoperatively. Six patients (aged 40-54 years), who completed a standard protocol of four consecutive treatments at 3-month intervals, were followed up at 6 months postoperatively. All patients (100%) reported marked (+3; +3 ~ −3) improvement of their overall bladder conditions. Mean bladder pain (from 8.2 to 1.7; range: 0 ~ 10), IC-related symptoms (from 18.5 to 5.7; range: 0 ~ 20), and bother (from 14.8 to 3.8; range: 0 ~ 16) improved significantly ( p < 0.01). The normalization of bladder mucosal morphology with treatments was remarkable under cystoscopic examination, and no significant adverse events were found. The cultured mesenchymal stem cells from Nanofat samples of the six patients were verified in vitro. Our preliminary results suggest novel intravesical therapy with autologous Nanofat plus PRP grafting is safe and effective for refractory IC/BPS. Surgical efficacy might be attributed to an in vivo tissue engineering process.